Differences In Teeth And Mouth Hygiene By Brushing Teeth Using A Mirror And Without A Mirror In Class V And VI Students Of SDN 12 Koto Tinggi - Anses Warman; Arnetty Arnetty; Ika Ifitri (International Journal Of Health Science, 2024)
Dental and oral diseases that are commonly found in Indonesia are dental caries and swollen gums. Children aged 10-14 years in West Sumatra experienced dental caries by 41.47% and swollen gums by 11.30% caused by plaque. Plaque prevention is done by brushing your teeth thoroughly and regularly. Mirror As a tool for brushing teeth can see the entire surface of the teeth so that maximum accuracy and cleanliness are obtained. This study aims to determine the difference between brushing teeth using mirror aids and without mirror aids in grade V and VI students of SDN 12 Koto Tinggi. Research method "quasi-experiment". The sample of this study was 36 people with inclusion criteria. The results showed dental and oral hygiene, brushing teeth using mirror aids amounted to 22.2% bad criteria and 77.7% good criteria, while without using a mirror 77.2% bad criteria and 22.7% good criteria. The result of the statistical test p value = 0.01 (P value < 0.05) means that there is a significant difference between brushing your teeth using a mirror and mirrorless aids. The conclusion in this study is that it helps reduce plaque numbers compared to without using mirror aids.